Aplikasi Metode Backward Chaining untuk Mengenali Kerusakan Mesin Mobil - ., admin (Zenit, 2015)
Car machine failures are vehicle problems commonly found in big cities. Due to lack of knowledge, people sometimes make a mistaken conclusion about the car problems. In this research, asystem was developed to obtain the real cause of such car machine failures by using backwardchaining inference method. The system utilized an expert system approach which was infered from rule-based knowledge. The knowledge was acquired from literature study and expert interviews. Incontrast to forward-chaining method which starts from a set of facts to make a conclusion, backwardchaining method starts from a conclusion to be proved by supported facts. The use of this system is performed simply by answering some questions according to the problems identification. As a result,the system gives conclusions that are collected from car problems generated from inferences. Outcomes of this study may help to overcome car problems, especially for Honda Accord Cielo used as a study case.Keywords: Backward-chaining, problems identification, car machine failures